Strategi STP (Segmenting, Targeting, Positioning) dalam Pendidikan Dasar: Pendekatan Edupreneurship untuk Meningkatkan Diferensiasi dan Daya Tarik Sekolah - Refi Mariska; Muhammad Affan Habibie; Mochamad Iskarim (Journal Innovation In Education, 2024)
Primary education is a fundamental element in the development of students' character and skills, and is recognized as an internationally recognized human right. However, the challenges in increasing the attractiveness and differentiation of primary schools are getting more complicated, especially in the midst of fierce competition. This study aims to investigate the application of STP (Segmentation, Targeting, Positioning) strategy in the context of basic education, by utilizing the edupreneurship approach. Edupreneurship offers innovative solutions to improve the quality and relevance of education by adopting entrepreneurial principles. This study uses a qualitative method with a literature study approach that analyzes various studies related to STP marketing strategies and the implementation of edupreneurship in elementary schools. The results of the study show that the segmentation of the basic education market can be carried out based on geographic, demographic, psychographic, and behavioral factors of students and parents. The right target market is identified through an analysis of the needs of parents and students related to the quality of education, the reputation of the school, and the values offered. Meanwhile, effective positions focus on differentiating relevant curricula, facilities, and extracurricular programs, which can increase the school's attractiveness. These findings show that the implementation of STP strategies integrated with the edupreneurship approach is not only able to attract the attention of parents and students, but also increase the competitiveness of primary schools in the education market.